Response of Growth and Production of Soybean Varieties Edamame ( Glycine max L. Meriil) To Super Compost Fertilizer and POC JST - Ade Fipriani Lubis; Turi Handayani; Vanny Erlangga (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
This research was conducted at the Experimental Field of the Faculty of Agriculture, Asahan University (UNA) Kisaran, Asahan Regency, North Sumatra, in February - April 2022. This study was arranged based on a factorial randomized block design (RBD) with 2 treatment factors and 3 replications. The first factor was the treatment of super compost (K) with 3 levels, namely K0 = 0 tons/ha (control), K1 = 5 tons/ha (0.94 kg/plot), K2 = 10 tons/ha (1 .88 kg/plot). Rhizobium Biological Fertilizer per 250 g of soybean seeds. The second factor is the concentration of JST POC (J) with 4 levels, namely J 0 = 0 ml/litre of water/plot, J 1 = 15 ml/litre of water/plot (1.5%), J 2 = 30 ml/litre of water/ plot (3%), J 3 = 45 ml/litre of water/plot (4.5%). The results showed that the treatment of compost had a significant effect on the concentration of POC ANN (J), which significantly affected the height of plants 3 weeks after transplanting, the number of branches 3 weeks after transplanting, the number of filled pods per sample plant, pod production per sample, and pod production per plot. The best plant height 3 weeks after transplanting at a dose of 1.88 kg of super compost (K 2 ) is 30.73 cm, the number of branches aged 3 weeks after transplanting is best at a dose of 1.88 kg of super compost (K 2 ), i.e. 8.40 branches, the best number of filled pods per sample plant at a dose of 1.88 kg of super compost (K 2 ) is 50.53 pods, the best pod production per sample is at a dose of 1.88 kg of super compost (K 2 ) i.e. 31.43 g, the best product per plot at the dose of super compost (K 2 ) is 0.30 kg. POC ANN concentration treatment (J) significantly affected plant height 3 weeks after transplanting, number of branches aged 3 weeks after transplanting, number of filled pods per sample plant, pod production per sample, and pod production per plot. The best plant height at 3 weeks after transplanting with POC ANN treatment with a concentration of 4.5% (J 3 ) is 29.23 cm, and the best number of branches aged 3 weeks after transplanting is best with POC ANN treatment with a concentration of 4.5% (J 3 ) namely 7.81 branches, the best number of filled pods per sample plant with POC ANN concentration of 4.5% (J 3 ), namely 48.76 pods, the best pod production per sample with POC ANN treatment of 4.5% (J 3 ) namely 29.89 g and the best production per plot with POC ANN treatment with a concentration of 4.5% (J 3 ) is 0.31 kg. The interaction of super compost fertilizer and POC ANN concentrations did not affect all parameters of the edamame soybean variety